MULTIMEDIA TECHNOLOGIES IN THE EDUCATIONAL PROCESS OF A HIGHER EDUCATION INSTITUTION - Idiyeva Lola Ismatovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
As we know at present, one of the promising areas of educational process improvement is the application of multimedia technologies. The article is about the analysis of the literature on the problems of the study that shows that there are many different definitions of the concept of "multimedia".